THE DEVELOPMENT OF THE ‘MYSTERY BOX’ METHOD IN SCIENCE EDUCATION TO ENHANCE LEARNING MOTIVATION AMONG PRIMARY SCHOOL STUDENTS - Fajar Fitri Utami; Tri Murwaningsih; Joko Daryanto (SOSIOEDUKASI, 2026)
IPAS teaching in primary schools tends to be teacher-centred, meaning that pupils’ motivation to learn is not yet optimal. The lack of variety in teaching materials results in limited pupil engagement in the learning process. This study aims to (1) analyse the IPAS learning process, (2) develop the ‘Mystery Box’ teaching aid, and (3) test the effectiveness of this teaching aid in enhancing pupils’ motivation to learn. The study employed the 4D model of research and development, comprising the Define, Design, Develop, and Disseminate stages. The research subjects consisted of an experimental class at SDN 01 Delingan and a control class at SDN 04 Bejen. Data collection techniques included observation, learning motivation questionnaires, interviews, and documentation. The results indicated that the Mystery Box medium is suitable based on validation by media experts, subject matter experts, and language experts. The results of the effectiveness test showed that student learning motivation in the experimental class was higher than in the control class in terms of the indicators of learning perseverance, active engagement, perseverance in the face of difficulties, interest in the material, and a positive attitude towards